A study on abnormal variation in the infratemporal region of human skull: An ossified pterygospinous ligament - JAI PRABHU.S.P; PRABHU.K (International Journal of Pharma and Bio Sciences, 2019)
The pterygospinous ligament is a ligament attached superiorly to the bony spur at the posterior border of lateral pterygoid plate and inferiorly to the spine of sphenoid. Occasionally this ligament may get ossified and forms a foramen called foramen of civinini which lies along the vicinity of the foramen ovale. The aim of the present study was to determine the incidence and variations in the ossified pterygospinous ligament. The study was carried out in RVS Dental College, Coimbatore on 50 adult dry human skulls to observe ossified pterygospinous ligament. Out of 50 skulls, 4% of the skull showed completely ossified pterygospinous ligament, 10% was incompletely ossified and 2% showed a complete pterygospinous bar. All these ossifications observed were unilateral and none of the skull showed bilateral ossification. The proximity of ossified ligament and foramen of civinini to foramen ovale may compress or entrap the mandibular nerve which might lead to Mandibular neuralgia. Therefore, knowledge of variations in the ossified pterygospinous ligament may help in the proper diagnosis of mandibular neuralgia. In conclusion, although the existence of ossified ligament is common but its occurrence should not be negligible.